Experimental Study on Heat Transfer Characteristics of a Parallel Mini-channel Direct Cooling Plate - Hu Lingren; Fang Yidong; Yang Wenliang; Xu Dan; Su Lin; Li Kang (Zhileng xuebao)
As a key part of two-phase cooling systems, direct cooling plates have received increasing attention with the development of two-phase cooling technology. A parallel mini-channel direct cooling plate was designed based on the experimental system of pumped two-phase cooling. The channel area of the cold plate was 140 mm long and 50 mm wide, having 21 parallel mini-channel, each 1.5 mm × 1.5 mm, separated by a fin with a thickness of 0.5 mm. The heat transfer characteristics of a parallel mini-channel direct cooling plate under different refrigerant inlet temperatures, flow rates, and heat fluxes were investigated. The variations in the local wall temperatures and heat transfer coefficients in different regions of the cooling plate were analyzed. The results indicate that when the heat flux is 0.5 W/cm2, the inlet temperature of the refrigerant is 15℃ the flow rate is 150 kg/h, and the wall temperatures in different channels rise monotonously along the flow direction. After the heat flux was increased to 6 W/cm2, the wall temperature first increased along the flow direction and then stabilized at a certain value. The wall temperatures of the middle channel were higher than those of the peripheral channel. The local heat transfer coefficient shows little variation under low heat flux, while an increase along the flow direction can be observed near the outlet of the mini channel under higher heat flux owing to the nucleate boiling, and the maximum increase in the heat transfer coefficient was 21%. Similar to the wall temperatures, the local heat transfer coefficient of the peripheral channel is higher because of the more intense flow boiling, with a maximum increase of 24%.